Plant polysaccharides in neuroprotection: mechanistic insights across central nervous system disorders - Yu, Qiyue; Chen, Hui; Qu, Zhuofeng; Qu, Jialin; Wang, Yan; Liang, Lina; Hu, Shouyu (Frontiers in Pharmacology, 2026)
Central nervous system (CNS) disorders pose a major global health burden, and the limited efficacy and adverse effects of current pharmacotherapies underscore the need for more effective therapeutic strategies. Plant polysaccharides, as key bioactive metabolites of medicinal plants, have attracted increasing attention due to their broad biological activities and favorable safety profiles. In this review, we comprehensively summarize recent advances in understanding their neuroprotective effects, emphasizing mechanistic pathways that include the suppression of neuroinflammation, mitigation of oxidative stress, inhibition of neuronal apoptosis, modulation of autophagy, and maintenance of gut microbiota homeostasis. These mechanisms are examined across diverse preclinical models, with particular attention to model selection, dosing parameters, and experimental rigor to ensure reliable interpretation. Furthermore, we critically discuss major challenges hindering clinical translation, including structural heterogeneity, limited bioavailability, and restricted CNS penetration, while highlighting emerging solutions such as advanced delivery systems and targeted chemical modification. Overall, this review delineates the multi-pathway neuroprotective actions of plant polysaccharides and offers strategic direction for future mechanistic studies and translational development.